Struktur dan Fungsi Sosial dalam Ungkapan Larangan Melaut dan Bertani di Kabupaten Pesisir Selatan - Intan Sri Utami; Zulfadhli Zulfadhli (Jurnal Bahasa dan Sastra, 2020)
This study aims to describe the social structure and function of people's beliefs, expressions of the prohibition of livelihoods and social relations about fishing and farming in the Kanagarian Kapuh Kecamatan Koto XI Tarusan Kabupaten Pesisir Selatan Regency. This type of research is a qualitative research with descriptive methods. The data of this study are the people's belief in expressions of prohibition of livelihoods and social relations between going to sea and farming in the Kanagarian Kapuh Kecamatan Koto XI Tarusan Kabupaten Pesisir Selatan. Data is collected from informants through recording techniques of prohibition, recording, observation, and interview. Based on the results of research and discussion that has been done it can be concluded that; (1) The structure of popular belief expressions prohibition is divided into two, namely the structure of two parts and the structure of three parts; (2) The social function of popular belief expressions prohibition is divided into four parts, namely, functioning as a thickening of religious emotions, functioning as a projection system, functioning as prohibiting, and functioning as educating.